The human problems of an industrial civilization - Mayo, Elton (London Routledge, 2003)
In this volume Mayo discusses the Hawthorne experiments, relating the findings about human relations within the Hawthorne plant to the social environment in the surrounding Chicago area. The Chicago School of Sociologists were studying aspects of social disorganization and this was a topic pioneered by Emile Durkheim.
Includes a description of the experiments undertaken by the Western electric company at its Hawthorne works in Chicago.
Keywords: Western Electric Company